Stock Waqf as an Innovation of Productive Waqf in Strengthening Institutional Regulation and Economic Potential in Indonesia - Alya Shofiana Rizka; Lathif Hanafir Rifqi (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2026)
Stock waqf represents an innovation in productive waqf, connecting Islamic philanthropy with Sharia-compliant capital market instruments. However, its implementation in Indonesia remains constrained by fragmented regulations, unclear institutional responsibilities, uneven nazhir capacity, and capital-market risks. This study aims to analyze the legal construction, institutional governance, operational models, economic potential, and implementation challenges of stock waqf from the perspective of Islamic economic law. It employs a normative juridical method using statutory and conceptual approaches. Primary legal materials include Indonesian waqf legislation, implementing regulations, and DSN-MUI fatwas concerning shares and Islamic capital-market instruments, while secondary materials consist of books, journal articles, official reports, and relevant research. The materials were analyzed qualitatively through systematic legal interpretation and descriptive-analytical techniques. The findings demonstrate that the legality of stock waqf is constructed through the intersection of waqf law and Sharia capital-market regulation rather than through a specific stock-waqf regime. Indonesian law recognizes shares as movable waqf assets, but the operational rules governing custody, corporate actions, asset substitution, risk mitigation, reporting, and ongoing Sharia compliance remain incomplete. Stock waqf may be implemented through direct share endowment, dividend waqf, cash waqf invested in Sharia securities, and the endowment of Sharia mutual-fund units. Its optimization requires integrated institutional coordination, professional nazhir management, transparent reporting, digital security, and prudent investment governance. This study contributes an integrated legal-governance framework for balancing the preservation of the waqf corpus with sustainable public benefits.